2004
DOI: 10.1111/j.1365-2966.2004.07799.x
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale wind structures in OB supergiants: a search for rotationally modulated Hα variability

Abstract: We present the results of a long-term monitoring campaign of the Hα line in a sample of bright OB supergiants (O7.5-B9) which aims at detecting rotationally modulated changes potentially related to the existence of large-scale wind structures. A total of 22 objects were monitored during 36 nights spread over six months in 2001-2002. Coordinated broad-band photometric observations were also obtained for some targets. Conspicuous evidence for variability in Hα is found for the stars displaying a feature contamin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 65 publications
9
81
0
3
Order By: Relevance
“…The C iiλλ6578, 6582 transitions also appeared to vary in both strength and the RV of the line centroid between observations, with changes in the profiles of both species observed over the shortest timescale probed (45 d) 7 . In comparison, the early B supergiants HD 14134 (B3Ia) and HD 43384 (B3Iab) also showed a rapid (≤14 d) transition from Hα absorption to emission (Morel et al 2004), although neither they nor the other B2-4 supergiants from that study demonstrated variability in the C ii lines. These transitions are temperature dependent and are absent in supergiants earlier than B0.7 and later than B9 and peak at B3, although their apparent abundance dependance have precluded their use as an accurate diagnostic ).…”
Section: The Mid-late B Super-/hypergiantsmentioning
confidence: 97%
See 1 more Smart Citation
“…The C iiλλ6578, 6582 transitions also appeared to vary in both strength and the RV of the line centroid between observations, with changes in the profiles of both species observed over the shortest timescale probed (45 d) 7 . In comparison, the early B supergiants HD 14134 (B3Ia) and HD 43384 (B3Iab) also showed a rapid (≤14 d) transition from Hα absorption to emission (Morel et al 2004), although neither they nor the other B2-4 supergiants from that study demonstrated variability in the C ii lines. These transitions are temperature dependent and are absent in supergiants earlier than B0.7 and later than B9 and peak at B3, although their apparent abundance dependance have precluded their use as an accurate diagnostic ).…”
Section: The Mid-late B Super-/hypergiantsmentioning
confidence: 97%
“…The origin of the latter is uncertain, with both photospheric and binary origins advanced for the quasi-periodic line profile variability observed in e.g. EZ CMa (=WR6; Morel et al 2004;Georgiev et al 1999), although apparently unambiguous binary modulation has been reported in a number of WR colliding wind systems by Stevens & Howarth (1999).…”
Section: The Wolf Rayetsmentioning
confidence: 99%
“…H α profile) and UV (e.g. P-Cygni lines) observations of galactic objects have revealed in recent years (for example Prinja et al 2002;Kaufer et al 2002;Morel et al 2004;Prinja et al 2004). Whilst the variability in the H α profiles of some of these Galactic objects may correspond to considerable changes in the properties of the winds, without further observations of the SMC objects we cannot investigate the extent of their variability (if any) and the subsequent affect on the derived wind parameters.…”
Section: Mass-loss: Observations and Predictionsmentioning
confidence: 99%
“…There are many exceptions to this general rule (see more examples in Davies et al 2005, Appendix A). In many cases, variable Hα emission is taken as evidence for binarity (e.g., Thaller 1997), but monitoring of a few luminous OB supergiants has shown that important changes can happen on very short timescales (Morel et al 2004). This behaviour has also been observed amongst the brightest OB supergiants in Wd 1 .…”
Section: A31 Classification In the I-bandmentioning
confidence: 99%